KOMUNIKASI PEMASARAN GRAND ZURI HOTEL DALAM MENGHADAPI PERSAINGAN PASAR DI KOTA PADANG SUMATRA BARAT - Solfarino, Tito; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Grand Zuri Hotel Padang is a property to 13 of Zuri Hospitality Management (ZHM) managed by Zury Hospital Management (ZHM) which was inaugurated on December 22, 2012. ZHM is a hotel management chain plus focusing in the field of hospitality. Zury Hospitality Management (ZHM) own and operate 12 hotels scattered in Pekanbaru, Dumai, Duri, Padang, BSD, Jababeka, Palembang, Lahat, Lippo Cikarang and Cipanas. While some other hotels too are being and will be constructed in several Big Cities in Indonesia. This study aims to determine To determine which dialkukan permsaran shopped faces competition covers how sales promotion, advertising and personal selling is done Grand Zuri Hotel Padang in the face of competition.Komunikasi Pemasaran Grand Zuri Hotel dalam menghadapi persaingan pasar di kota Padang Sumatra Barat.This study used a qualitative method with descriptive approach. This research was conducted at the Hotel Grand Zuri Padang, West Sumatra, which is located on the street M. Thamrin No. 25 211 27 Padang West Sumatra. There are six informants were taken for this study. The types and sources of data obtained through primary data and secondary data. Collecting data with, interview, observation and documentation. This study uses data analysis Miles and Huberman interactive with data validity checking is done through the extension of participation and triangulation.The results of this research sales promotion undertaken Grand Zuri Hotel Padang in the face of the competition is to make tresho-tresho and using social media that they have to do promotion, started using facebook, instagram, path, twitter and their fans page. Advertising undertaken Grand Zuri Hotel Padang is by advertising prodak them creatively to attract the attention of customers. Selected media in advertising is radio, newspapers and magazines. Radio they choose is Sushi FM, which was played as many as five times a day. The print media use only magazine devoted service to advertise the hotel only and use Singgalang newspapers for promotion and advertising. Selling performed while personal Grand Zuri Hotel Padang in competition is to do salles call. Salles call conducted every day except on Saturday and Sunday. The strategy every day morning and afternoon staff salles hotel executives came out to meet directly with their consumers. Starting from the travel agent, the company swsata and government offices.Keywords: Marketing Communication, Marketing Communication Elements and Grand Zuri Hotel